Socio-Demographic Characteristics, Nutrition Profile and Health Related Practices of Soliga Tribes in Karnataka, India (Indian Journal of Public Health Research & Development, 2021)
Nutritional status is an important influence on overall health and wellbeing of a population. One of thevulnerable group is tribal population. The main tribe found in Karnataka is Soliga tribal community,majority of them have low economic status. Hence, malnutrition can be the most common condition arisingin this community due to inadequate intake of dietary nutrients. In this purposive, free-living study, thedetailed information on the population distribution, nutritional status, nutrient intake of Soliga community(30-65 years) were assessed using standardised questionnaires which included health and lifestyle relatedKnowledge, Attitude and Practice (KAP) questions. Anthropometric measurements were assessed usingstandard method. The dietary and nutrient intakes were collected using food frequency questionnaires and24-hour dietary recall method. The tribal colonies mainly depended on minor forest produce and manuallabour for livelihood, and majority of the study population were economically deprived. The BMI was normalin men, whereas women were undernourished. The 24-hour dietary recall data revealed that the subjectsfollowed 2 major meals, about 97% population consumed mixed type of diet, the intake of macronutrientswas lower than the recommended dietary allowances. The KAP survey revealed that subjects possessed goodhealth and hygiene related knowledge and attitude, but poorly practiced. Constant monitoring of nutritionalstatus and bridging the gaps in nutritional KAP of the tribal population can provide early warning of anydeterioration in their health and nutritional status, hence facilitating effective planning and implementationof nutrition interventions in this unique population.
Keywords: Soliga tribes, Nutrient intake, Nutritional status, Knowledge, Attitude and Practice (KAP), Primitive Tribes, RDA.